Rabies in non-hematophagous bats in São José do Egito, semi-arid of Pernambuco (Research, Society and Development, 2021)
Several species of mammals in Brazil have already been diagnosed with the rabies virus among companion, farm and wild animals. Among the bats, the hematophagous Desmodus rotundus stands out, however, the record of positives is not restricted to this food guild. Therefore, this work aims to report the positive records of rabies in bats in the municipality of São José do Egito, located in the semi-arid region of Pernambuco. An analysis of records with data on samples submitted for rabies analysis by sanitary surveillance and by the work of monitoring the bats performed in the municipality between on October / 2010 and July / 2012 was carried out. Eleven specimens of three species (Molossus molossus, Myotis lavali and Glossophaga soricina) were found in four years, positive for rabies in St. Joseph of Egypt with a higher register for M. molossus. In one of the cases it happened to the aggression to a citizen. The specimens were found in atypical conditions maintaining daytime activity, lying on the ground still alive or dead on the street and in their shelters. The records show that rabies circulates in the urban area of the municipality and that monitoring is necessary to avoid contagion to humans and domestic animals.